Penerapan Artificial Intelligence (AI) Pada Sistem Informasi Optimasi Jadwal Kuliah Menggunakan Algoritma Genetika - Dedi Prasetio; Wawan Hermawan Syah; Budi Budi (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
Scheduling lectures is one important aspect to support the implementation of lectures. With the scheduling of lectures, lecture time can be arranged, so that the room can be used effectively. To arrange lecture scheduling, it is of course needed the right way so that arranging the lecture schedules becomes easier and faster. At the College of XXXX, lecture schedules is still done in the conventional way that is arranging the schedule manually using Microsoft Excel software so that it takes a long time in preparing the scheduling of lectures. To simplify and accelerate the process of preparing lecture schedules optimally, the Lecture Scheduling Information System is one of the right solutions. Genetic Algorithm is one way to make logical and systematic steps so that the Information System Scheduling lectures can provide solutions that are easy, faster and more optimal. The genetic algorithm is one of the advances in the field of information technology in the field of Artificial Intelligence (AI) that can solve optimization problems. So that the process of making a schedule using genetic algorithms prepares lecture schedules faster, more precise and optimal. The results obtained from the modeling of genetic algorithms in the lecture schedules system include reguler morning class schedules, reguler evening class schedules, and extention class schedules in all majors at XXXX Higher Education.